Experimental Adaptation of Murine Norovirus to Calcium Hydroxide - Oishi, Wakana; Sato, Mikiko; Kubota, Kengo; Ishiyama, Ryoka; Takai-Todaka, Reiko; Haga, Kei; Katayama, Kazuhiko; Sano, Daisuke (Frontiers in Microbiology, 2022)
Slaked lime (calcium hydroxide) is a commonly used disinfectant for fecal sludge. Although viruses are inactivated by lime treatment, whether RNA viruses adapt to lime treatment has not yet been determined. Here, we show that murine norovirus developed higher tolerance during serial passages with lime treatment. We compared synonymous and non-synonymous nucleotide diversities of the three open reading frames of viral genome and revealed that virus populations were subjected to enhanced purifying selection over the course of serial passages with lime treatment. Virus adaptation to lime treatment was coincident with amino acid substitution of lysine to arginine at position 345 (K345R) on the major capsid protein VP1, which accounted for more than 90% of the population. The infectious clones with the K345R produced using a plasmid-based reverse genetics system exhibited greater tolerance in a lime solution, which indicated that the specific amino acid substitution was solely involved in the viral tolerance in lime treatment.